STUDY ON THE ANALYSIS OF THE ACTUAL STAGE OF KNOWLEDGE OF INTERFERENCE BETWEEN ACCOUNTING INFORMATION AND THE MANAGEMENT OF THE ECONOMIC ENTITY - Ciuhureanu, Alina (Annales Universitatis Apulensis Series Oeconomica, 2017)
Not often managers or administrators of economic entities „run away” from everything that means accounting and accounting information. It is a reality of our days in the circumstances in which the accounting information is necessary for the fulfillment of the management functions. Accounting, through the information provided, has an active and decisive role in management and provides the working language of business, indispensable for analyzing the entity’s activity and results, which is objectively necessary to be done in financial terms. Starting from this reason, the article presents the results obtained from a selective research carried out on a sample of 301 economic entities within the Center Region, whose objective was to identify the respondents’ opinions on the interference between the accounting information and the management of the economic entity.